2019
DOI: 10.3389/fphar.2019.00711
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Combination of N-Palmitoylethanolamide, Beta-Caryophyllene, Carnosic Acid, and Myrrh Extract on Chronic Neuropathic Pain: A Preclinical Study

Abstract: Neuropathic pain (NP) is a common public health problem that poses a major challenge to basic scientists and health-care providers. NP is a complex problem with an unclear etiology and an often-inadequate response to current medications. Despite the high number of drugs available, their limited pharmacological efficacy and side effects hamper their chronic use. Thus, the search for novel treatments is a priority. In addition to pharmaceuticals, natural extracts and food supplements are often used to help treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 79 publications
(108 reference statements)
1
13
0
Order By: Relevance
“…Gabapentinoids like pregabalin and gabapentin represent a first-line treatment in chronic neuropathic pain and represent one of the most widely used drugs to control this condition. However, patients usually used higher doses for pain control which resulted in wide range of adverse effects [24].…”
Section: Discussionmentioning
confidence: 99%
“…Gabapentinoids like pregabalin and gabapentin represent a first-line treatment in chronic neuropathic pain and represent one of the most widely used drugs to control this condition. However, patients usually used higher doses for pain control which resulted in wide range of adverse effects [24].…”
Section: Discussionmentioning
confidence: 99%
“…CA is widely used as a food preservative and protective agent, and it is used in the nutritional healthcare and cosmetic industries due to its fragrance and antibacterial activity. In addition, studies have shown that CA can reduce lipid oxidation, and exhibits great potential for the protection of nerves and the treatment of obesity-related diseases [ 17 , 18 , 19 ]. However, its effects on mammalian reproductive processes, especially in female ovarian development and early embryonic development, are still unclear.…”
mentioning
confidence: 99%
“…However, valproate exerts its effects by increasing the concentrations of GABA via inhibiting its metabolism and increasing its synthesis ( 75 ). Therefore, there is still a significant and positive association between an increase in the oxidative stress markers and a decrease in the antioxidant levels with the number of seizures in valproate monotherapy ( 65 ).…”
Section: Discussionmentioning
confidence: 99%